On the Dynamics of a Nonautonomous Predator-Prey Model with Hassell-Varley Type Functional Response - Yan Zhang; Shujing Gao; Kuangang Fan (Abstract and Applied Analysis)
The dynamic behaviors of a nonautonomous system for migratory birds with Hassell-Varley type functional response and the saturation incidence rate are studied. Under quite weak assumptions, some sufficient conditions are obtained for the permanence and extinction of the disease. Moreover, the global attractivity of the model is discussed by constructing a Lyapunov function. Numerical simulations which support our theoretical analysis are also given.